Assisted e-commerce as a tool to gap digital divides : possibilities of adapting the Indian model to Finnish environment - Sorsa, Karina (My University, 2019)
Digitalization of services is a current trend and services and products are being increasingly digitalized. Still, there are large amounts of people with either no means, skills or will to use information systems. Such digital divide between digital “haves” and have-nots” is a global problem and is causing inequalities. Although Finland is one of the most digitally connected countries in the world, the problem of digital divide is present here as well. Especially it is the problem for elderly population in sparsely inhabited areas, as the services are being digitalized and physical outlets are centralized to larger centres. In India the digital gap is vast and number of people with insufficient skills, hardware or infrastructure is large. To bridge this gap, a business model of assisted e-commerce has emerged. It combines virtual services with assistant and works on the side of a physical business, providing the skills, hardware and trust for its user. This research aims to clarify the concept of assisted e-commerce for transferability to another environment and researches the attitudes of elderly population in Finland for such a business model to gap the digital divide for them. The empirical part of this research is based on thematical interviews in India and Finland. As the concept of assisted e-commerce is relatively new, two interviews have been conducted with Indian developers of assisted e-commerce concept to clarify the model and get an understanding, how the model can be modified for transferability to another environment, for example, Finnish. The core finding was, that the assisted e-commerce is a light service which can be integrated on the side of another physical store without excessive inputs required from the agent. In Finland goal of the inter-views was to find out the attitudes and current use of digital services among people of age 65+ years. The interview topic was considered very uncomfortable and the people were either reluctant to talk about digital related topics or had very strong negative opinions towards them. The assisted e-commerce model is very versatile and can contain almost any services that can be digitalized. The assistant can be either physical person, or virtual with video or chat support. The largest hindrance for adapting the service model in Finland is the attitudes of potential user group, who often select in their day to day lives a more expensive, time-consuming and ineffective method of dealing when there is a digital option provided. The elderly tend to be reluctant to use the digital devices, have little or none interest for learning to use new digital services or have no courage for operating with online services. Family and other close social networks influence is important in encouraging for digital service use, but the priority still seems to be operating with a “real” person.
Keywords: digital divide, assisted e-commerce, digitalization